1999
DOI: 10.1099/00221287-145-12-3465
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular survival of Burkholderia cepacia complex isolates in the presence of macrophage cell activation

Abstract: Strains of the Burkholderia cepacia complex have emerged as a serious threat to patients with cystic fibrosis due to their ability to infect the lung and cause, in some patients, a necrotizing pneumonia that is often lethal. It has recently been shown that several strains of the B. cepacia complex can escape intracellular killing by free-living amoebae following phagocytosis. In this work, the ability of two B. cepacia complex strains to resist killing by macrophages was explored. Using fluorescence microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
129
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 54 publications
7
129
1
Order By: Relevance
“…The capacity of Bcc strains to survive and replicate within eukaryotic cells may explain their persistence in the respiratory system . However, the replication ability of Burkholderia inside cell lines is known to vary between isolates or genomovars (Saini et al, 1999;Sajjan et al, 2006). In this study we showed that both B. ambifaria HSJ1 wild-type and variant can replicate within phagosomes, but HSJ1v clearly displayed reduced replication in the human monocyte cell line compared with HSJ1.…”
Section: Features Of B Ambifaria Clinical Isolatesmentioning
confidence: 61%
See 1 more Smart Citation
“…The capacity of Bcc strains to survive and replicate within eukaryotic cells may explain their persistence in the respiratory system . However, the replication ability of Burkholderia inside cell lines is known to vary between isolates or genomovars (Saini et al, 1999;Sajjan et al, 2006). In this study we showed that both B. ambifaria HSJ1 wild-type and variant can replicate within phagosomes, but HSJ1v clearly displayed reduced replication in the human monocyte cell line compared with HSJ1.…”
Section: Features Of B Ambifaria Clinical Isolatesmentioning
confidence: 61%
“…Direct evidence of intracellular survival of the Bcc species has been shown in airway epithelial cells, in murine macrophages, in human monocytic cells and in amoebae (Marolda et al, 1999;Saini et al, 1999;Savoia and Zucca, 2007). The capacity of Bcc strains to survive and replicate within eukaryotic cells may explain their persistence in the respiratory system .…”
Section: Features Of B Ambifaria Clinical Isolatesmentioning
confidence: 99%
“…In addition, B. cepacia complex strains can survive within a murine macrophage cell line in the presence of an oxidative burst, and reduced nitric oxide production (Saini et al, 1999). These observations suggest that bacterial resistance or adaptation to oxidative damage may play a role in the infectivity and persistence of B. cepacia complex strains within the airways of patients with cystic fibrosis (Valvano et al, 2005).…”
Section: Introductionmentioning
confidence: 75%
“…Previously, we have shown that B. cepacia complex strains can survive intracellularly in both macrophages and amoebae (Lamothe et al, 2004;Marolda et al, 1999;Saini et al, 1999). In addition, B. cepacia complex strains can survive within a murine macrophage cell line in the presence of an oxidative burst, and reduced nitric oxide production (Saini et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that B. cepacia is capable of survival and growth within free-living amoebae, indicating that amoebae may be a reservoir for B. cepacia in the environment [26,27]. The mechanism by which B. cepacia survives in amoebae and pulmonary macrophages might be similar [16]. Furthermore, the pathogenic potential of B. cepacia for non-CF patients has been illustrated in patients with chronic granulomatous disease.…”
Section: Discussionmentioning
confidence: 99%